Functional outcome of long-arm cast versus double sugartong splint in acute paediatric distal forearm fractures: A randomised controlled trial - Banjade, Deepak; Adhikari, Sushan; Adhikari, Rabindra; Tamang, Ramesh Syantan; Dahal, Saroj Chandra; Lamichhane, Megha Raj (Journal of Kathmandu Medical College, 2022)
Background: The treatment of choice for paediatric distal forearm fractures has been a long-arm cast (LAC) following closed reduction. An alternative treatment is to use a double sugar-tong splint (DSTS), found equally effective to provide three-point fixation and comparable outcomes to cast. Objectives: To compare the functional outcome between LAC and DSTS for the treatment of paediatric distal forearm fractures. Methods: A randomised controlled trial was done among 36 patients of 5-15 years with acute distal forearm fractures without neurovascular deficit treated with LAC and DSTS recruited by convenience sampling at a tertiary care centre after ethical approval. Acceptability of reduction, loss of reduction, union rates, cast comfort, range of motion and complications were studied at follow-up upto 12 weeks and analysed using SPSS v.11.5. Results: Among a total of 36 patients, 18 cases were treated by the LAC method and others by the DSTS method. Both LAC and DSTS were comparable in the maintenance of reduction, the remanipulation rate was 8.3% (n = 3), not significant (p-value = 0.967). All had a union at six weeks follow-up. No statistical difference in mean VAS score (p-value = 0.524), mean loss of flexion (p-value = 0.397), and mean loss of pronation/supination (p-value = 0.814). No statistically significant difference in activities of daily living was noted. No complications were encountered. Conclusion: DSTS is safe and as effective as LAC in the treatment of distal forearm fractures in children, identical in terms of functional outcome, maintenance of reduction, complications, and time to union.